Consumer Culture Theory's future in marketing - Rokka, Joonas (Journal of marketing theory and practice, 2021)
This commentary offers a view into the contributions of Consumer Culture Theory (CCT) in marketing and charts promising future avenues for research and marketing practices building a culturally sensitive and reflexive approach. After highlighting pioneering CCT perspectives, an outline for future directions in marketing is offered emphasizing the assembling of experiences, shaping of brands' symbolic universes, institutional and creative market processes, and networked and algorithmic mediation of consumption ideologies and desires. Overall, CCT's future looks promising in its commitment and ability to foster critical, contextually sensitive, and reflexive cultural insights into marketing - an important foundation for marketing strategy and practices.